2007
DOI: 10.1158/0008-5472.can-07-0418
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Consequences of Cyclin D1 Overexpression in Prostate Cancer Progression

Abstract: The cyclin D1 oncogene encodes the regulatory subunit of a holoenzyme that phosphorylates and inactivates the Rb protein and promotes progression through G 1 to S phase of the cell cycle. Several prostate cancer cell lines and a subset of primary prostate cancer samples have increased cyclin D1 protein expression. However, the relationship between cyclin D1 expression and prostate tumor progression has yet to be clearly characterized. This study examined the effects of manipulating cyclin D1 expression in eith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 47 publications
5
59
0
2
Order By: Relevance
“…It plays an essential role in the development and progression of several cancers including breast, esophagus, bladder, and lung cancer (Lin et al 2000, Musgrove 2006, He et al 2007. Our results showed that in MCF-7 cells, a high-glucose condition led to decreased expression of cyclin D1 compared with a normal-glucose condition (Fig.…”
Section: Alteration In Expression Of Cyclin D1 By High Glucose and Inmentioning
confidence: 51%
“…It plays an essential role in the development and progression of several cancers including breast, esophagus, bladder, and lung cancer (Lin et al 2000, Musgrove 2006, He et al 2007. Our results showed that in MCF-7 cells, a high-glucose condition led to decreased expression of cyclin D1 compared with a normal-glucose condition (Fig.…”
Section: Alteration In Expression Of Cyclin D1 By High Glucose and Inmentioning
confidence: 51%
“…Similarly, SENP1 moderates the expression of the cell cycle regulator, cyclin D1; diminishing SENP1 in PCa cells decreases cyclin D1 levels (18). Previous studies indicate that enhanced expression of cyclin D1 is readily observed in advanced PCa (19,20) and contributes to PCa pro-gression (21,22). Therefore, the expression of SENP1 in PCa cells modulates major factors in PCa progression.…”
mentioning
confidence: 95%
“…There was no significant difference of p53 expression between the groups (LI: 11.86 ± 19.51 and 2.03 ± 2.27, respectively; p > 0.05) (Figures 1F1, F2). For most tumors (27/43), the expression intensity was weak or moderate (2)(3)(4)(5)(6)). An intense expression (9) was observed in three cases and it comprised over 60% of cancer cells.…”
Section: Statisticsmentioning
confidence: 99%
“…The proliferation rate, a feature that has been proven to be an unfavorable prognostic factor in many cancers, was evaluated using its two widely known indicators: Ki-67 (Mib-1) protein, which is expressed by proliferating cells during all active phases of the cell cycle, and cyclin D1, which is involved in controlling the G1/S phase [1][2][3].…”
mentioning
confidence: 99%
See 1 more Smart Citation